Peranan Lagu Berbantuan Aplikasi Suno sebagai Media Interaktif dalam Meningkatkan Hasil Belajar Bahasa Jerman Siswa - Akihary, Wilma; Maruanaya, Rita Fransina; Apituley, Patresia Silvana (Universitas Pattimura, 2025)
German is the second foreign language taught in high schools in Maluku. In its introduction, students have difficulty learning German vocabulary and structures. However, teachers always try to ensure that students can understand the material taught well, even though the differences between Indonesian and German make it still difficult to learn a new language. This makes teachers look for creative ways so that the material taught can be absorbed easily by students. For this reason, teachers need to design interactive media that is easy to access and use digital media that is familiar to high school students, who are currently known as Gen Z. This Community Service (PKM) is an assistance for teachers to teach German material by utilizing one of Suno's interactive digital media. In this service, the PKM team taught Uhrzeiten und Aktivitäten Material. Students were asked to compose a simple text related to the material Uhrzeiten und Aktivitäten. The text was then transferred into the Suno application. In the application, they can choose the desired music genre. Students can finally create an interesting and pleasing song by using the simple text they compiled. Through the song, students can remember the themes, vocabulary, and structures they have just learned. Consciously, they can pronounce the song according to German pronunciation. As a result, learning German as a foreign language becomes more meaningful and fun. Overall, this assistance has a positive impact not only on students but also on teachers. Learning becomes more meaningful and fun. Students can easily memorize the vocabulary taught because it is repeated according to the song genre they like. When the teacher practices it in class, she feels helped by the assistance material provided. The learning atmosphere became more fun and meaningful, and the students' German learning outcomes improved.